6(x-2)+x=5x-1

Simple and best practice solution for 6(x-2)+x=5x-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x-2)+x=5x-1 equation:



6(x-2)+x=5x-1
We move all terms to the left:
6(x-2)+x-(5x-1)=0
We add all the numbers together, and all the variables
x+6(x-2)-(5x-1)=0
We multiply parentheses
x+6x-(5x-1)-12=0
We get rid of parentheses
x+6x-5x+1-12=0
We add all the numbers together, and all the variables
2x-11=0
We move all terms containing x to the left, all other terms to the right
2x=11
x=11/2
x=5+1/2

See similar equations:

| 3c4= | | 3x+2+5x+12=180 | | K=2m=5 | | 3(-4)=-1/2(24-6x) | | 32=-8+8b | | 82+31+x=180 | | -7=x(-3) | | 29x+8=205 | | n/6=8/3 | | -161=7(5-4n) | | 3^2w^2-8^2=0 | | 4(×-2)=2(x-4)+2× | | 6k=19.8 | | 10x-4-2x=x+10 | | 7y-2y=24 | | 12=z/6-30 | | 40(4y-9)=5y | | 5(m+4)=-2(-4-m)+30 | | 3c–14=19 | | 4(3x+2)=-10 | | -v/5=6.4 | | n-16(-2)=-24 | | 2/3x+15=-5 | | a+1=15 | | 7w+21=91 | | h-4=h+9 | | x=-10000+Y | | 9t=–7+8t | | 6m+10=1m | | 3x+4=x+18= | | 6(2+k)-5=7 | | 4(2x−5)=−3(5−x) |

Equations solver categories